A neural hierarchy for illusions of time: Duration adaptation precedes multisensory integration - Heron, James (The Association for Research in Vision and Ophthalmology, 2013)
Perceived time is inherently malleable. For example, adaptation to relatively long or short sensory events leads to a repulsive aftereffect such that subsequent events appear to be contracted or expanded (duration adaptation). Perceived visual duration can also be distorted via concurrent presentation of discrepant auditory durations (multisensory integration). The neural loci of both distortions remain unknown. In the current study we use a psychophysical approach to establish their relative positioning within the sensory processing hierarchy. We show that audiovisual integration induces marked distortions of perceived visual duration. We proceed to use these distorted durations as visual adapting stimuli yet find subsequent visual duration aftereffects to be consistent with physical rather than perceived visual duration. Conversely, the concurrent presentation of adapted auditory durations with nonadapted visual durations results in multisensory integration patterns consistent with perceived, rather than physical, auditory duration. These results demonstrate that recent sensory history modifies human duration perception prior to the combination of temporal information across sensory modalities and provides support for adaptation mechanisms mediated by duration selective neurons situated in early areas of the visual and auditory nervous system (Aubie, Sayegh, & Faure, 2012; Duysens, Schaafsma, & Orban, 1996; Leary, Edwards, & Rose, 2008).